Assessing the impact of credit ratings and economic performance on firm default - Giulio Bottazzi; Marco Grazzi; Angelo Secchi; Federico Tamagni (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2007)
The study of firms' default has attracted wide interest among both practitioners and scholars. However, attention has often been limited to a relatively small set of financial variables. In this work, we try to increase the scope of analysis extending the investigation to other possible determinants of default. In particular, we rely on credit ratings to summarize firms' financial conditions, and we address the potential predictive power of a set of economic dimensions size, growth, profitability and productivity which industrial economics suggest to be meaningful determinants of survival. We present novel results based on a large Italian dataset reporting credit ratings for all the firms in the sample. As far as financial conditions and default are concerned, we find that the firms displaying the worst credit ratings are quite turbulent, but also exhibit non-negligible chances to recover. Moreover, the analysis of the distribution of firms' economic performance reveals that profitability stands up as the only relevant economic variable telling apart defaulting firms from surviving ones, at different time distance to default. Finally, probit and logit estimation of default probabilities, testing for the simultaneous effect of economic and financial dimensions, suggest that growth, in addition to credit ratings, significantly affects the likelihood of default, albeit in a positive (and as such unexpected) way in the manufacturing industry.
Keywords: C14; C25; D20; G30; L11; 330; Default probability; Credit ratings; Firm growth dynamics; Selection; Unternehmenserfolg; Betriebliche Kennzahl; Kreditwürdigkeit; Insolvenz; Wahrscheinlichkeitsrechnung; Theorie; Schätzung; Italien